Biogas Production Using Continuous Stirred Tank Reactor (CSTR) from Palm Oil Mill Effluent (POME) Utilizing Mesophilic Bacteria - Afrianti, Suratni; Zainal, Edwina (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Energy is essential for human life, yet dependence on fossil fuels and other non-renewable resources contributes to global energy crises and environmental degradation. Biogas is an environmentally friendly alternative that has the potential to partially replace fossil fuels. Palm Oil Mill Effluent (POME), which contains high concentrations of biodegradable organic matter, is a promising substrate for biogas production through anaerobic fermentation. This study aims to evaluate the potential of Palm Oil Mill Effluent (POME) as a substrate for biogas production using a Continuous Stirred Tank Reactor (CSTR) under mesophilic conditions (35–37oC). The experiment was conducted for 30 days with at a laboratory scale (10 L reactor volume). Feedstock characterization (COD, TSS, TS, VS, and pH) confirmed that POME has high organic content and slightly acidic conditions, supporting its suitability for anaerobic digestion. The results show that anaerobic fermentation of POME produced biogas with an average methane (CH4) concentration of 66–71%, indicating stable digestion performance and relatively high efficiency. These methane levels indicate stable digestion performance and relatively high process efficiency. Overall, the findings confirm that POME is a promising feedstock for biogas production and can contribute to renewable, environmentally friendly energy supply.